From territorial diagnosis to strategic intent. Knowledge brokerage and co-construction. Fieldwork Insights from Karst Landscapes – the poljes of Canton 10 (Bosnia and Herzegovina) - Crouteix, Orianne; Lerin, François; Vendé, Jérémy (VertigO)

(untitled) (Université du Québec à Montréal et Éditions en environnement VertigO, 2025)
This article defends the idea that with a territorial diagnosis, using an inductive and comprehensive approach, it is possible to develop an integrated and systemic approach, and to extract themselves from the thematic logics that constrain environmental action. Our diagnosis of the karstic area of Canton 10 in Bosnia-Herzegovina, combines three analytical frameworks from management science and geography: strategic analysis of environmental management, agrarian diagnosis and landscape approaches. We assume an environmental intentionality on and for the territory. Through our methodological tinkering and iterative work, we are emphasising (i) the importance and rarity of a unique hydro-geomorphological system, (ii) the need to involve agricultural stakeholders and understand the dynamics associated with the livestock system. Indeed, our diagnosis highlights crucial territorial dynamics that are often overlooked by top-down environmental projects, such as the presence of extensive pastoralism, significant disparities in habitat linked to the demographic, political and historical issues of the territory, and the development of so-called green energies. Paradoxically, and in contrast to the environmental conservation projects established in this area, carried out by international foundation which focus on a single polje (a large flat-bottomed karst depression) with national recognition, we suggest that action be taken at the cantonal level with international recognition. We then discuss the importance and limitations of these methodological tinkering, knowledge brokering, and this embedded approach.